Sabina Augusta an imperial journey - Brennan, T. Corey 1959- (Oxford University Press, 2018)
'Sabina Augusta' traces the development of Sabina's partnership with her husband, the emperor Hadrian (reigned 117-138), and shows the vital importance of the empress for Hadrian's own aspirations
Previously issued in print: 2018. - Includes bibliographical references and index
Keywords: Vibia Sabina / approximately 88-approximately 137; Hadrian / Emperor of Rome / 76-138; Sabina, Vibia -- Kaiserin, Römisches Reich -- ca. 86-136; Empresses / Rome / Biography; Rome / History / Hadrian, 117-138; Biografie